How do you know if you are making a difference? : a practical handbook for public service organisations. - Morton, Sarah (Policy Press, 2022)
This book sets out practical and theoretically robust approaches for understanding and tracking change that any organisation can use to evaluate their contribution to social change and become more efficient and effective.